The genome of the leaf-cutting ant Acromyrmex echinatior suggests key adaptations to advanced social life and fungus farming - Nygaard, Sanne; Zhang, Guojie; Schiøtt, Morten; Li, Cai; Wurm, Yannick; Hu, Haofu; Zhou, Jiajian; Ji, Lu; Qiu, Feng; Rasmussen, Morten; Pan, Hailin; Hauser, Frank; et al. (Genome Research, 2011)
We present a high-quality (>100× depth) Illumina genome sequence of the leaf-cutting ant Acromyrmex echinatior, a model species for symbiosis and reproductive conflict studies. We compare this genome with three previously sequenced genomes of ants from different subfamilies and focus our analyses on aspects of the genome likely to be associated with known evolutionary changes. The first is the specialized fungal diet of A. echinatior, where we find gene loss in the ant's arginine synthesis pathway, loss of detoxification genes, and expansion of a group of peptidase proteins. One of these is a unique ant-derived contribution to the fecal fluid, which otherwise consists of “garden manuring” fungal enzymes that are unaffected by ant digestion. The second is multiple mating of queens and ejaculate competition, which may be associated with a greatly expanded nardilysin-like peptidase gene family. The third is sex determination, where we could identify only a single homolog of the feminizer gene. As other ants and the honeybee have duplications of this gene, we hypothesize that this may partly explain the frequent production of diploid male larvae in A. echinatior. The fourth is the evolution of eusociality, where we find a highly conserved ant-specific profile of neuropeptide genes that may be related to caste determination. These first analyses of the A. echinatior genome indicate that considerable genetic changes are likely to have accompanied the transition from hunter-gathering to agricultural food production 50 million years ago, and the transition from single to multiple queen mating 10 million years ago.
10.1101/gr.121392.111